28 Colorectal Cancer Resections During COVID-19: To Do or Not to Do?. (12th October 2021) - Barter, R; Kalaiselvan, R
Abstract: Introduction: Ascertaining the practice of colorectal cancer (CRC) resections during the COVID-19 pandemic in England and Wales. Method: A list of all colorectal multi-disciplinary teams (MDTs) was obtained from the National Bowel Cancer Audit (NBOCA) database. A survey was designed using Google Forms and emailed to at least one consultant colorectal surgeon of each MDT. One response per MDT was used in the analysis. All responses were anonymous. Study duration was from 15 th April 2020 to 30 th June 2020. Results: Sixty-eight of the 150 MDTs enlisted on the NBOCA database in England and Wales responded. 86.6% were performing CRC resections and 86% were screening patients pre-operatively for COVID-19. 84.9% were using full Personal Protective Equipment (PPE - FFP3 and eye protection) in all cases whereas 12.3% were using PPE only in suspected cases. 44.4% had resorted to open resections due to risk of laparoscopy being an aerosol generating procedure. 13.7% attributed post-operative complications to COVID-19 and 4 centres reported death due to COVID-19 related complications. 40% of MDTs used short course radiotherapy in rectal cancer patients where resections were postponed either by patient or by the team. 55% responded to feeling uncomfortable/very uncomfortable to cancel cancer resections while 31.7% were equivocal and others comfortable not to operate during the pandemic. Conclusions: This survey demonstrates a snapshot of practice during the peak of the COVID-19 pandemic. The majority of the centres continued to perform CRC resections safely where possible. There has been obvious disruption to services and change to normal practice.